Synthesis of Isoxazolidinyl Epoxides by Oxone Treatment of 2,3-Dihydroisoxazoles in Acetone–Water Solution: A New Stereoselective Approach to Hydroxy-Substituted Isoxazolidines - Záborský, Ondrej; Štadániová, Radka; Doháňošová, Jana; Moncol, Ján; Fischer, Róbert (Synthesis, 2017)
A practical and efficient synthesis of new class of isoxazolidinyl epoxides by direct treatment of 4,5-unsubstituted 2,3-dihydroisoxazoles with Oxone and NaHCO3 in acetone/water solution is described. All epoxidation reactions proceed with excellent anti-selectivity and provide stable products in very good yields. A concept for the development of stereoselective approach to 3,4-trans-hydroxy-substituted isoxazolidines, namely triazole derivatives as important molecules in medicinal chemistry is presented. The synthesis is characterized by highly syn-stereoselective conversion of epoxides to anomeric bromoisoxazolidines, which are found to be powerful reaction intermediates for the coupling reactions with various nucleophiles.
Keywords: heterocycles; isoxazolidines; epoxides; triazoles; diastereoselectivity; aza-Michael addition; organocatalysis